STUDI EKSPERIMENTAL TERHADAP UNJUK KERJA KUDA-KUDA BAJA RINGAN PROFIL C DENGAN KETEBALAN 0,60 MM - anggraini, Irene; Yusuf, M; ., Elvira (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2014)
Since wood material is very difficult to find nowadays and the quality begin to decrease, then light gauge steel is chosen as an alternative of wood as a construction material roof truss. However, many types of light gauge steel in the market give a great influence to the specification and standardization of light gauge steel frame structure calculations . This testing the strength of the truss 0.6 mm thick C profile with a particular landscape . Loading test were performed on a truss structure using a full -scale model of the test object with incremental load . The structure of the truss that tested an easel structure with spans of 12 m, height 2.51 m , and a 20 tilt angle . Truss collapse when was given a load of 315 kg. With hanger and a heavy loaded bearing was 60 kg plus the weight of the cube as many as 17 pieces of heavy cube which is 15 kg. As for the collapse phenomenon is topchord buckling. From the collapse phenomenon, its been known that the structure of the truss suffered a failure behavior on cold formed steel rod of iron C is not due to shear or tensile strength screws . It can be seen that the screws which were used for 3 pcs of each knot point could not be separated from the strong connection and resist the force that was applied.